Stem cell therapy- An update - Rahman, Fazlur; Subedi, Bikash; Awal, Anisul; Haque, KMHS Sirajul; Siddique, Md Abu; Banerjee, Sajal Krishna; Safiuddin, Md; Ahmed, Chaudhury Meshkat; Ahsan, Syed Ali; Anam, Khairul; Ahmed, Md Khurshed; Rahman, Md Mukleshur; et al. (University Heart Journal, 2009)
Stem cells are one of the most fascinating areas of biology today. Stem cells have two important characteristics that distinguish them from other types of cells. First, they are unspecialized cells that renew themselves for long periods through cell division. The second is that under certain physiologic or experimental conditions, they can be induced to become cells with special functions. Stem cells can be obtained from several sources including spare embryos, special purposes embryos, aborted fetus, umbilical cords, adult tissue or organs, cadavers. The procedure of adult stem cell therapy involves several steps including extraction of cells from various sources, separation by surface markers using FACS, growth in specific culture media and injection into target organs. This modern aspect of regenerative or reparative medicine can be applied for cardiac diseases (coronary artery diseases, heart failure, non ischaemic cardiomyopathies), skin replacement, Diabetes, spinal cord injury, neurodegenerative disease like Parkinsonism, stroke. In future, it may become possible the use of stem cells in organ transplantation. Â Â  doi:10.3329/uhj.v4i2.2076 University Heart Journal Vol. 4 No. 2 July 2008 p.46-48